Analysis of the microbial flora in breast abscess: a retrospective cohort study conducted in the emergency department - Ramakrishnan, Ramya; Trichur, Ramakrishnan V.; Murugesan, Sowmya; Cattamanchi, Srihari (International Surgery Journal, 2017)
Background: Breast abscess develops as a complication of lactational mastitis. Recently, there is an increase in the incidence of non-lactational breast abscess. The aim of the study was to analyse the microbial flora in the lactational and non-lactational breast abscess in the ED and to elucidate the susceptibility of flora to different antibiotics. Methods: This is a retrospective cohort study of breast abscess patients registered in the ED over two years. The case records of these patients were retrieved, and the details of their age, clinical presentation, investigation, and treatment were recorded. Specifically, the pus culture sensitivity and antibiotics used in the management of these patients were noted, and the pattern of microbiological flora analyzed. Results: A total of 124 patients were included in the study, with 97 women were categorized into lactational breast abscess, and 27 women were classified as a non-lactational breast abscess. Mean age was 24 years of age (Range 18 to 56 years). The majority of the women were young between 18 and 34 years of age (83%). The culture was grown in 92% of the patient pus specimens. Staphylococcus aureus (83%) was common organisms cultured in lactational breast abscess. Mixed Flora including Staphylococcus aureus and Group B Streptococci were grown in non-lactational breast abscess. Conclusions: Appropriate antibiotic choices are of immense importance in the management of breast abscess. Mixed flora is common in non - lactational breast abscess when compared with a lactational breast abscess. Staphylococcus Aureus is the most common isolate in both groups.